2001
DOI: 10.1128/jcm.39.8.2784-2787.2001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mutations in the rpoB Gene Associated with Rifampin Resistance in Rhodococcus equi Isolated from Foals

Abstract: Treatment with a combination of erythromycin and rifampin has considerably improved survival rates of foals and immunocompromised patients suffering from severe pneumonia caused by Rhodococcus equi. Frequently, because of monotherapy, emergence of rifampin-resistant strains has been responsible for treatment failure. Using consensus oligonucleotides, we have amplified and sequenced the rifampin resistance (Rif r )-determining regions of 12 rifampin-resistant R. equi strains isolated from three foals and of mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
44
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 20 publications
(16 reference statements)
1
44
2
Order By: Relevance
“…A mutation in the rpoB gene (codon 526, His526Asp) associated with rifampin resistance was confirmed by partial sequencing (6). An A-to-G mutation at position 2063 in domain V of the 23S rRNA gene of R. equi resulted in the high-level macrolide resistance of the isolated strains (7).…”
mentioning
confidence: 92%
“…A mutation in the rpoB gene (codon 526, His526Asp) associated with rifampin resistance was confirmed by partial sequencing (6). An A-to-G mutation at position 2063 in domain V of the 23S rRNA gene of R. equi resulted in the high-level macrolide resistance of the isolated strains (7).…”
mentioning
confidence: 92%
“…PCR and DNA sequencing in the rpoB gene were performed for eight R. equi isolates from eight AIDS patients with pneumonia or lung abscess caused by R. equi between 1998 and 2001 as described previously (5). A set of primers, MF (5Ј-CGACCACTTCGGCAACCG-3Ј) and MR (5Ј-T CGATCGGGCACATCCGG-3Ј), was chosen to amplify a portion of the rpoB region of R. equi that includes the rifampin resistance-determining region.…”
Section: Methodsmentioning
confidence: 99%
“…However, the emergence of rifampin resistance in R. equi has been reported (10,17), although it is still rare. Recently, Fines et al reported that several mutations in the rpoB gene are associated with rifampin resistance in R. equi isolated from foals, as well as in Mycobacterium tuberculosis, Escherichia coli, and Staphylococcus aureus (5).…”
mentioning
confidence: 99%
“…A combination of rifampin and erythromycin remains the treatment of choice for foals, but no optimal drug regimen has been established for human infections and relapse is a significant problem (52). Moreover, rifampin-resistant phenotypes of R. equi have been identified (1,12,49), and the use of erythromycin in foals may have side effects (13, 46). There thus remains a need to identify physiological features of R. equi that contribute to the ability of this organism to thrive within macrophages and which might provide targets for the implementation of novel therapeutic strategies.…”
mentioning
confidence: 99%